FIRST RECORD OF THE GENUS ARCTICOCARCINUS SHWEITZER ET AL., 2016 (DECAPODA: BRACHYURA) IN THE DANIAN OF THE CRIMEA (UKRAINE) AND ITS PALEOBIOGEOGRAPHIC SIGNIFICANCE - Dernov, V.; Udovychenko, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The Paleogene decapod crustaceans of Ukraine are insufficiently studied. This group of arthropods has not attracted much attention of researchers, despite the fact that the remains of decapods are known in the Paleogene sediments of the Dnipro River area, Donetsk Basin, the Crimea and the Ukrainian Carpathians. The article describes the first find of a decapod crustacean of the genus Arcticocarcinus Schweitzer et al, 2016 in Ukraine. The fossil comes from the lower part of the Danian of the Crimea (Ak-kaya Section near the Bila Skelia, Bilogirsk District). The fossil was found in situ in the decapod burrow Thalassinoides Ehrenberg, 1944. Such finds allow us to establish which fossil decapod crustaceans produced burrows Ophiomorpha, Thalassinoides, and Spongeliomorpha. Sediments with crab remains were accumulated in the environment of Skolithos Ichnofacies. This ichnofacies is usually confined to areas of the seabed whose sediments are constantly mixed by waves. There was a cold-water paleobasin on the territory of modern northern Ukraine in the Danian Age. This basin was connected to the Western European paleobasin and the Boreal paleobasin. The southern basin, located in the Carpathians, the Black Sea Depression, and the Crimea, was much warmer and closely connected with the Mediterranean Basin. A representative of the genus Arcticocarcinus was first found outside Sweden. It is very unlikely that the genus Arcticocarcinus Schweitzer et al, 2016 entered modern Sweden from the Crimea or vice versa via the Polish Channel, as the Carpathian flysch basin was obviously a barrier. Apparently, the exchange of fauna took place through the Dnipro-Donetsk Sea and the Pripyat Strait. These basins were part of the so-called "Sea of Arkhangelskyi" (a large sublatitudinal basin that stretched from the spurs of the Caucasus and the Urals to Western Europe). Arcticocarcinus cf. insignis (Segerberg, 1900) expands the paleontological characteristics of the Danian of Crimea and testifies to the free exchange of benthic faunas of North-Western Europe and Crimea.